Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1097/01.mjt.0000433951.09030.5a
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events Associated With the Treatment of Multidrug-Resistant Tuberculosis

Abstract: Multidrug-resistant tuberculosis (MDR-TB) is a growing public health problem. Due to long duration of therapy and concurrent use of multiple second-line drugs, adverse drug events (ADEs) are regarded as the most important clinical consideration in patients undergoing anti-MDR-TB treatment. To evaluate the frequency and type of treatment-related ADEs owing to MDR-TB therapy. The Cochrane Library, MEDLINE, and EMBASE were searched from inception through October 1, 2012, with additional manual search of Internati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
61
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 18 publications
11
61
3
1
Order By: Relevance
“…First, insomnia was the most common ADR and one of the most bothersome, yet sleep disturbances were rarely documented in previous studies on MDR-TB ADRs. 9 Another noteworthy finding was that neither depression nor anxiety was ever documented in the medical records. Even though both depression and anxiety are common ADRs during MDR-TB treatment, 30 psychiatric symptoms are often overlooked by clinicians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, insomnia was the most common ADR and one of the most bothersome, yet sleep disturbances were rarely documented in previous studies on MDR-TB ADRs. 9 Another noteworthy finding was that neither depression nor anxiety was ever documented in the medical records. Even though both depression and anxiety are common ADRs during MDR-TB treatment, 30 psychiatric symptoms are often overlooked by clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…8 The majority of studies on MDR-TB treatment-related ADRs have been retrospective cohorts utilizing medical record data abstraction of clinician report of ADRs. 9 Several studies outside the MDR-TB context have shown a lack of concordance between patient report and clinician medical record documentation. 10ā€“14 …”
mentioning
confidence: 99%
“…334,335 However, high-quality, prospective studies of adverse effects in children on MDR tuberculosis treatment are rare. Additionally, adverse effects are more difficult to assess in children, and could therefore be underestimated.…”
Section: Renal Diseasementioning
confidence: 99%
“…Serious drug-related adverse effects associated with DR-TB therapy include irreversible hearing loss, hypokalaemia, renal damage, hypothyroidism, depression and psychosis, while unpleasant effects include tinnitus, nausea and vomiting, joint pain, vertigo, peripheral neuropathy, anxiety and confusion. 26 In patients with HIV co-infection, adverse events do not appear to be more common, but can be more difficult to diagnose and manage, due to overlapping drug toxicities with ART. 25 27 While adverse effects associated with DR-TB therapy have been well documented in adults, 26 they have been underinvestigated in young children, [28][29][30] although treatment appears to be better tolerated than in adults.…”
Section: Discussionmentioning
confidence: 99%
“…26 In patients with HIV co-infection, adverse events do not appear to be more common, but can be more difficult to diagnose and manage, due to overlapping drug toxicities with ART. 25 27 While adverse effects associated with DR-TB therapy have been well documented in adults, 26 they have been underinvestigated in young children, [28][29][30] although treatment appears to be better tolerated than in adults. TB-associated stigma, 31 prolonged hospitalisation and repeated painful injections may also leave psychological scars.…”
Section: Discussionmentioning
confidence: 99%